Answer :

a2 – a = 2 + 4 ( nCx = nCy n = x + y or x = y )


a2 – a – 6 = 0


a2 – 3a – 2a – 6 = 0


a(a – 3) + 2(a – 3) = 0


(a + 2) (a – 3) = 0


a = -2 or a = 3


But, a = -2 is not possible since it’s negative.


So, a = 3.

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Prove that the prRD Sharma - Mathematics

There are 10 lampMathematics - Exemplar

If n+1RS Aggarwal - Mathematics

If nC<RS Aggarwal - Mathematics

Fill in the BlankMathematics - Exemplar

Fill in the BlankMathematics - Exemplar

The number of wayMathematics - Exemplar

Total number of wMathematics - Exemplar

The number of wayMathematics - Exemplar

The number of triMathematics - Exemplar